(untitled) (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2026)
In the era of globalization, many fields, including aesthetics within philosophy, have undergone significant changes. Centuries-old standards of inner and outer beauty have been replaced by false, artificial standards that have negatively impacted people’s aesthetic tastes. This article conducts a comparative study of the secular and religious foundations of beauty, and analyzes it as one of the weapons of “mass culture”.